Nitrous oxide emission from conservation forest of Kampar Peninsula peatland ecosystem: Emisi gasN2O dari hutan konservasi lahan gambut Semenanjung Kampar - Nardi; Anwar, Syaiful; Yani, Mohamad; Nurholis; Hendrizal, Muhammad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Nitrous oxide (N2O) is a long-lived greenhouse gas with a warming potential of 300 times higher than CO2. Conserving of intact peat swamp forest can hold the natural physical and chemical properties of the soil, such that the N2O emission occurs naturally. To quantify N2O emission from peatland ecosystems, data availability is highly needed. The objectives of this study were to quantify the emission of N2O and determine the main factors controlling N2O emission from peatland conservation forests. This research was conducted from January to December 2020 in the Kampar Peninsula, Pelalawan Regency, Riau Province. This study found that N2O emission at peatland conservation forest was 0.23 ± 0.19 kg-N/ha/year. Substantial changes in soil and environmental factors such as water table, soil temperature, soil moisture, water-filled pore space, NH4-N, and NO3-N significantly affect the exchange of N2O between peatlands and the atmosphere.